美日中小學教學研究實施經驗之啟示 Reflections on Implementing Japanese Lesson Study in the United States - 廖淑戎 Liao, Shu-Jung (National Changhua University of Education, 2008)
在傳統日本教學研究裡所實施的學課研究，自1999 年開始迅速地散播在美國許多的學校。學課研究是教學改善的專業發展活動，焦點放在專業性協同合作、同儕觀察、自我反思、批判討論如何進一步增進學生學習，它提供教師機會學習教學。然而，在美國適用的困難性與其所遭遇的挑戰，卻因兩國教學文化的殊異性而顯現出來。有鑑於此，本文將透過文獻探討，討論在美國實施的困難，並依據其遭遇的挑戰，提出幾點對台灣教師專業發展的建議。 Research lessons, which take place within traditional Japanese lesson studies, have spread rapidly to many US schools since 1999. Lesson study is a form of teaching improvement that focuses on engaging in professional collaboration, peer observation, self-reflection, and critically discussing how to further enhance student learning. It provides the opportunity for teachers to learn about their own teaching as much a culture as a professional development activity. However, Japan and the US have vastly different educational systems. There are challenges in adapting Japanese Lesson Study for an American context. By the method of literature study, how lesson study can be adapted to be difficult in the United States are discussed. According to the challenges of lesson study in the United States, some suggestions on teachers' professional development in Taiwan are offered.